Tourism and culinary: study of identification & tourism development strategy of Pagerharjo village, Samigaluh District, Kulonprogo Regency - Teddy Chandra; Teddy Chandra (Universitas Merdeka Malang, 2022)
Pagerharjo Village is one of the villages within the working area of the Borobudur Authority Agency, an agency under the supervision of the Ministry of Tourism and Creative Economy / Tourism and Creative Economy Agency. Pagerharjo Village is trying to become a tourist village that is able to attract as many tourist visits as possible in order to improve the welfare and standard of living of the community for the better through tourism. Tourism and Culinary: Study of Identification Tourism Development Strategy of Pagerharjo Village, Samigaluh District, Kulonprogo Regency is a research conducted with the objectives: 1) to find out the description of Pagerharjo village, Samigaluh District, Kulonprogo Regency as a tourist destination; 2) to find out the description of Pagerharjo village tourism destinations, Samigaluh District, Kulonprogo Regency as a tourist destination; and 3) to find out the culinary description of Pagerharjo village, Samigaluh sub-district, Kulonprogo district as a tourist destination. This research was conducted using qualitative research methods with descriptive analysis. Data collection is done by means of literature document study, observation, and interviews. The results showed that Pagerharjo village has several potential tourist attractions, namely Nglinggo tourist village, Nglinggo tea garden, Ngisis Hill, Nglinggo viewing post, and also potential culinary tourism, namely ingkung megono, taro criping, pegagan criping, banana criping, various wedhang spices, traditional roast tea, deplok coffee, and geblek. For the development of the Pagerharjo tourism village, it is recommended that the village government intensify promotional activities and also synergize with all tourism sector stakeholders.